Reporting Regulation and Private Firms' Bank Credit - MORETA, ANTONIO (Journal of Accounting Research, 2026)
ABSTRACT This paper studies the effect of reporting regulation on private firms' bank credit and its economic consequences. I exploit the Spanish institutional setting, which provides a unique combination of confidential loan data and regulatory features that generate quasi‐exogenous variation in reporting regulation. Using a regression discontinuity design, I find that firms subject to incremental reporting regulation obtain more bank credit primarily through cash flow–based lending, term loans, and long‐term debt, without higher interest rates. These findings are explained by stronger banking competition and greater reliance on financial statement data. However, firms do not expand their net financial position, as bank credit substitutes for other liabilities, and exhibit weaker performance consistent with the costs of reporting regulation. This evidence from a different setting offers new insights into how reporting regulation influences credit contracting for private firms and strengthens the empirical basis for policy‐making.